Clinical and genetic analysis of MOCOS gene-related hypouricemia - Peng, Huifang; Tu, Ping; Ma, Qiaobo; Tang, Jinpeng; Xiao, Wannv; Hu, Xinyu; Zhang, Yingyu; Jiang, Hongwei (Frontiers in Genetics, 2025)
BackgroundUric acid is an important metabolic end-product in the human body, and metabolic abnormalities involving uric acid are receiving increasing attention.MethodsThis study involved clinical assessment and genetic testing of a 40-year-old male patient who presented with the main complaint of hypouricemia for 7 years.ResultsIn addition to hypouricemia, the patient showed low urinary uric acid levels, low uric acid excretion rate, and nephrolithiasis. His younger brother also showed extremely low serum uric acid levels. Trio-whole-genome sequencing (trio-WGS) showed that the proband and his younger brother had a compound heterozygous molybdenum cofactor sulfurase (MOCOS) genotype with the pathogenic variant c.1272T>A (p.Cys424Ter) and the likely pathogenic variant c.1418C>T (p.Ser473Leu). The final diagnosis was Xanthinuria type II. A review of the literature for cases of Xanthinuria type II revealed reports describing 25 patients from 17 families. All 25 patients showed very low serum uric acid levels, eight showed urinary tract stones, and three reported joint or limb pain. Truncation pathogenic or likely pathogenic variants of the MOCOS gene accounted for nearly half of the cases, and p.Arg419Ter and p.Thr349Ile were the two most frequent variants. The p.Cys424Ter variant reported in this study is a new pathogenic site that has not been reported previously.ConclusionSustained low serum uric acid levels may indicate monogenic uric acid metabolism disorders, and these patients should undergo genetic testing. In patients diagnosed with xanthinuria type II caused by MOCOS gene variants, the use of purine drugs should be prohibited to avoid serious adverse events. Given the severe defects in the MOCOS gene-deficient mouse model, additional research is needed to clarify the clinical profile of Xanthinuria type II and the other roles of MOCOS in metabolic pathways.